FEATURES OF IMMUNE RESPONSE IN PATIENTS WITH DIFFERENT HISTOLOGICAL TYPES OF RENAL CELL CARCINOMA - L. М. Kurtasova (SPb RAACI, 2014)
Abstract. We have examined ninety-three patients with locally advanced renal cell cancer at the age of 45 to 55 years. Immunological testing was performed before radical nephrectomy and 14 days after surgery. The cellular and humoral immune parameters and cell chemiluminescence were studied both at baseline and in stimulated cells. We found changes of immunophenotypic profile of blood lymphocytes, serum immunoglobulin indexes and chemiluminescence response of blood neutrophils, dependent on tumor histology.